The influence of Papacarie use on direct restorations marginal seal - Pineda Mejia, Martha (2008)
The purpose of the investigation was, to compare the marginal seal of direct restorations, carried out with the sandwich technique, after the removal of decayed tissue by means of papaine gel (Papacarie) and the conventional rotational method. So, 20 recently extracted human premolars were selected, with decay lesions that committed the oclusal and proximal surface. The sample was randomly divided in two groups: Group 1: the removal of decayed dentine was made, by means of the chemo mechanical technique using the gel Papacarie. Group 2: the removal of decayed dentine was made by means of the conventional technique, using rotational instruments. After the removal of decayed tissues by both techniques a direct restoration was placed using the sandwich technique, placement of glass ionomer modified by resin, adhesive system of a single step and micro hybrid composite resin. Then, after term cycling process, the specimens were subjected to passive filtration of blue methylene dye, for 3 days, cut through the mesiodistal way, and observed by stereoscopic microscope, according to degrees of blue methylene dye filtration at toothrestoration interface, in oclusal and gingival margins of the preparation. The analysis of results indicated that: gel Papacarie permited the effective removal of decayed tissues for preparing restoration’s cavities, however, it significantly influenced in a higher frequency of dye filtration, committing marginal sealing of restorations, compared with the rotational method of conventional removal.